Microstructure, phase transformations and properties’ evaluation of Al-Si-Ni metastable alloys - Nitoi, Alexandra; Bedo, Tibor; Varga, Bela; Pop, Mihai Alin; Munteanu, Daniel (Elsevier BV, 2019)
Additive manufacturing is a technology which has the potential to replace conventional casting methods. The versatility delivered by this process is of great interest, mainly due to the capacity to manufacture complex shapes, as well as the multitude of materials which can be used. Generally, the metallic powders used in additive manufacturing are obtained by gas atomization, meaning that the alloys solidify rapidly from the melt pool. This phenomenon determines both the improvement of mechanical properties, due to the finishing of the structure, as well as potentially obtaining metastable structures in the form of supersaturated or amorphous/nano solid solutions. Aluminium-based metallic glasses are of interest due to their combined high specific strength to weight ratio, good ductility and superior corrosion resistance. The paper presents results concerning the microstructural evolution for bulk, melt-spun ribbons. Al-Si-Ni alloys (Al70-Si18-Ni12, Al68-Si18-Ni14,Al66-Si18-Ni16). It was observed that structural transformations during heating, starting from metastable structures (melt-spun ribbons), generate significant amounts of energy. This phenomenon could be of practical importance in the use of metallic powders in additive manufacturing technology.
Keywords: metastable alloys; melt spinning; exothermal phase transformation.